Minimally Invasive Ways to Monitor Changes in Cardiocirculatory Fitness in Running-based Sports: A Systematic Review - Schimpchen, Jan; Correia, Paulo Freitas; Meyer, Tim (International Journal of Sports Medicine, 2022)
This systematic review provides a synthesis of research investigating submaximal protocols to monitor changes in cardiocirculatory fitness in running-based sports. Following PRISMA guidelines, 2,452 records were identified and 14 studies, representing 515 athletes, satisfied the eligibility criteria. While most studies found large associations between changes in heart rate at standardized, submaximal running speeds and changes in aerobic fitness (r=0.51–0.88), three studies failed to establish a relationship (r=0.19–0.35). The intensity of the submaximal protocols seems to be relevant, with changes in running speeds at 90% of maximal heart rate showing larger relationships with changes in aerobic fitness (r=0.52–0.79) compared to 70% of maximal heart rate (r=0.24–0.52). Conversely, changes in post-exercise heart rate variability were very largely associated with changes in aerobic fitness when the testing protocols were less intense (70% of maximal heart rate) (r=0.76–0.88), but not when the test required participants to achieve 90% of their maximal heart rate (r=−0.02–0.06). Studies on post-exercise heart rate recovery revealed inconclusive results (r=−0.01– −0.55), while rate of heart rate increase may be a promising athlete monitoring metric (r=0.08– −0.84) but requires further research. In summary, when executed, analyzed, and interpreted appropriately, submaximal protocols can provide valuable information regarding changes in athlete cardiocirculatory fitness.
Keywords: non-invasive; invisible; endurance; team sports